ANALISIS SENTIMEN PENGARUH COVID-19 TERHADAP KEHIDUPAN BERMASYARAKAT PADA MEDIA SOSIAL TWITTER MENGGUNAKAN K-NEAREST NEIGHBOR - Pascal Aldwin Hernando (2021)
Coronavirus Disease (COVID-19) is a pandemic that occurs due to the spread of the newly discovered coronavirus. COVID-19 is spread through saliva or objects that come out of the nose of an infected person coughing or sneezing. With the emergence of this pandemic, the whole world, including Indonesia, has experienced a setback in various fields of life. With this COVID-19, the government has imposed a lockdown in various areas which has caused everyone's activities to be limited from home. To reveal the situation during the lockdown, people use social media as an intermediary, one of which is Twitter. With so many uses of twitter, making data related to COVID-19 for sentiment analysis using the classification K-Nearest Neighbor. By referring to certain areas, namely Jakarta and Surabaya, data were collected for testing with KNN. The results of the test show that the Jakarta data get the best accuracy at 79.85% with a value of K = 9, while the Surabaya data get the best accuracy at 76.47% with a value of K = 11, 17, 19, 20.